Model partnerstwa uczelni wyższych z podmiotami otoczenia konkurencyjnego: The model of the partnerships between universities and entities of their competitive environment - Stefaniuk, Tomasz (Management and Administration Journal, 2021)
The paper focuses on the problems of university partnerships with entities of its competitive environment. It was made an identification of the university environment, paying attention to necessity of constant planning of develop partnerships between universities and the environment. It also presents examples of activities that universities can take to developing partnerships with the competitive environment.